Paradigma Thomas Kuhn dan Relevansinya Terhadap Perkembangan Keilmuan Islam di Indonesia - Rahman, Taufik (JURNAL AL-AQIDAH, 2021)
Paradigm has an important in science. According to Kuhn, the paradigm is very influential on the steps and results of research. Because a paradigm is a pattern or framework of thinking adopted by scientists in conducting research. This article will explain Thomas Kuhn's paradigm and its relevance toward Islamic thought in Indonesia. This article is library research using a historical-philosophical approach. The historical-philosophical approach use to see the development of Islamic thought in Indonesia and analyze or find the relevance of Thomas Kuhn's paradigm concept toward the development of Islamic thought in Indonesia. The results show that the paradigm concept of Thomas Kuhn can be used in Islamic scholarship in Indonesia to produce Islamic thought that is relevant to current issues.